Influence of Culture Conditions on Ex Vivo Expansion of T Lymphocytes and Their Function for Therapy: Current Insights and Open Questions - Sudarsanam, Harish; Buhmann, Raymund; Henschler, Reinhard (Frontiers in Bioengineering and Biotechnology, 2022)
Ex vivo expansion of T lymphocytes is a central process in the generation of cellular therapies targeted at tumors and other disease-relevant structures, which currently cannot be reached by established pharmaceuticals. The influence of culture conditions on T cell functions is however incompletely understood. For clinical applications of ex vivo expanded T cells, so far relatively classical standard cell culture methodology has been established. The expanded cells have been characterized in both preclinical models and clinical studies mainly using a therapeutic endpoint, e.g. anti-tumor response and cytotoxic function against cellular targets. Whereas the influence of manipulations of T cells ex vivo including transduction and culture expansion has been studied to a much lesser detail, or in many contexts remains unknown. This includes the circulation behavior of expanded T cells after intravenous application, their intracellular metabolism and signal transduction, their cytoskeletal (re)organization or their adhesion, migration and subsequent intra-tissue differentiation. This review aims to provide an overview of established T cell expansion methodologies and to address unanswered questions relating in vivo interaction of ex vivo expanded T cells for cellular therapy.